The Story Telling as a Solution of Student’s Difficulties in English Speaking at Islamic of Senior High School Sirojut Tholibin - Nafa Wardana Lutfah; Kustiana Arisanti; Ririn (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Speaking is one of the most important of the four skills namely listening skills, speaking skills, reading skills and writing skills. Talking is one action to convey information and express ideas and feelings. This research is conducted to describe students' difficulties in speaking English lessons, factors that make it difficult for students to speak English, and students strategies to overcome their difficulties in speaking English lessons in twelfth grade MA Islam Sirojut Tholibin 2022/2023. This study uses a qualitative method. MA Sirojut Tholibin class XII IPA selected by the researcher as a sample consisting of 32 students. In collecting data, researchers used observation, interviews, and questionnaires. Data collected analyzed by reducing data, presenting data, drawing conclusions and verification. Researchers use the results of the pretest and posttest, to show reliability data. From the data analysis, the researcher found that each student was different difficulty in speaking, there is lack of vocabulary, poor pronunciation, nothing to say, lack of motivation, fear of being wrong, shy, using mother tongue. There are factors that cause difficulties in speaking English in English lessons. Other factors are internal factors, students do not have an interest in learning to speak, classroom conditions, student environment. Students have strategies for coping their difficulty in speaking. Students join English clubs or English courses for improve their speaking, so they can practice speaking English and ask them friend or teacher to improve their English. Students memorize vocabulary and write short stories to improve their speaking skills. Keyword: English Speaking, Student’s Difficulties, Solution